2015
DOI: 10.1007/s10157-015-1099-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of fractional magnesium excretion (FEMg) as a predictor of interstitial nephropathy and its correlation with conventional parameters

Abstract: Our findings may indicate that the combination of the FEMg and the NAG index can provide a specific, sensitive assessment for TIN in patients without renal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Glomerular filtration of Mg decreases as CKD progresses, whereas tubular reabsorption of Mg is impaired due to tubulointerstitial injury, thus causing an increase in fractional Mg excretion [17,18]. However, the quantitative excretion of Mg tends to decrease regardless of the compensatory increase in fractional Mg excretion if glomerular filtration rate (GFR) falls to < 30 mL/min/ 1.73 m 2 [19], particularly < 10-15 mL/min/1.73 m 2 [20,21].…”
mentioning
confidence: 99%
“…Glomerular filtration of Mg decreases as CKD progresses, whereas tubular reabsorption of Mg is impaired due to tubulointerstitial injury, thus causing an increase in fractional Mg excretion [17,18]. However, the quantitative excretion of Mg tends to decrease regardless of the compensatory increase in fractional Mg excretion if glomerular filtration rate (GFR) falls to < 30 mL/min/ 1.73 m 2 [19], particularly < 10-15 mL/min/1.73 m 2 [20,21].…”
mentioning
confidence: 99%
“…Fractional excretion of magnesium level is a significant predictor of glomerular disorder or tubulo‐interstitial nephropathy. A recent study by Noiri et al () revealed a negative correlation between FEMg level and eGFR among paticipants with an eGFR of less than 30 mL/min. However, this study showed a significant negative correlation between FEMg level and eGFR among participants with normal eGFRs.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the highest mean of FEMg (7.96 ± 4.08%) was found in the highest PTH quartile (> 89.5pg / mL). According to Dai et al [28], PTH improves the absorption of magnesium in the distal contoured tubule and the increase in FEMg in patients with CKD in the early stages, works as a compensatory mechanism to keep serum serum Mg levels within the normal range [29]. In CKD, studies on the relationship between PTH and serum Mg were preferably performed in dialysis patients and showed an inverse association between these variables [30,31], but prospective studies on this effect in non-dialysis patients are lacking.…”
Section: Discussionmentioning
confidence: 99%